The Influence of Price, User Experience, and Service Innovation on the Decision to Use Transjakarta Transportation Modes - Hermawan, Herman; Handayani, Langgeng Sri (Review: Journal of Multidisciplinary in Social Sciences, 2025)
Increasing urbanization in Jakarta demands an efficient and affordable transportation system. This study aims to determine the relationship between price, user experience, and service innovation to the decision of TransJakarta transportation mode users. This study used a quantitative method with 100 respondents of TransJakarta users in Bekasi. Data processing was performed using SPSS26. Multiple linear regression analysis showed that price had a positive and significant effect on usage decisions, and service innovation also had a positive and significant effect. However, user experience had a positive but insignificant effect. The regression model explains 81.2% of usage decisions. Recommendations are given to improve service quality, set competitive prices, and develop innovations to attract more users and reduce congestion. The originality of this research lies in its specific case study on students of Universitas Pelita Bangsa Class of 2021 in Bekasi, providing in-depth insights from a potential user segment.